Application of Plant Growth Promoting Rhizobacteria (PGPR) Dosage on Growth and Production of Lettuce (Lactuca sativa L.) - Yoga Wahyudi Putra; Fedri Ibnusina; Alfikri Alfikri (Agrosains : Jurnal Penelitian Agronomi, 2023)
Lettuce plants belong to short-lived vegetable crops. Lettuce has different sizes of shapes and color of leaves according to the variety. The purpose of this study was to identify the dose of PGPR administration to the growth and production of lettuce plants, analyze the appropriate dose of PGPR application for lettuce plant growth and production and analyze the results of lettuce plant business analysis with PGPR doses. This research was carried out during the months of March to May 2022. The implementation of this research activity was carried out at the Payakumbuh State Agricultural Polytechnic. This study used an experimental method with Completely Randomized Design (CRD). The treatment used is such as inorganic fertilizer, PGPR by 300 and 350 ml. There were 504 populations, 3 treatments with 6 tests, 18 beds and 90 plant samples, data analyzed using analysis of variance with a further test of Duncan’s Multiple Range Test 5%. Business analysis is measured by calculating total costs, revenues, R/C ratio, BEP price, BEP production, profit and profitability. The results showed that with inorganic fertilizer treatment, PGPR by 300 and 350 ml differed markedly from leaf width, root length and fresh weight of plants and did not differ markedly from plant height and number of leaves. The treatment with the highest average value was found in the use of PGPR 350 ml with an average yield on plant height parameters with a value of 20.95 cm, leaf width of 13.13 cm, number of leaves 16.4 strands, root length of 12.41 cm and fresh weight of plants 102.9 g at plant age of 5 week after application. This research found that the application of PGPR by 300 and 350 ml were not significantly different in the observed variables of plant height and number of leaves, but they were significantly different in the observed variables of leaf width, root length and weight fresh plants.